(untitled) (Research, Society and Development, 2022)
Abuse of alcohol has been increasing among the female public in recent years and consumption in a harmful way can trigger several damages and is considered a public health problem associated with the increase in violence involving both sexes. This integrative literature review article aims to present, based on data in the literature, the scientific evidence that points to brain damage in pre-clinical studies using female rats after exposure to ethanol. For this, the article sought to answer the following guiding question, "What do pre-clinical studies in female rats point out about alcohol consumption and changes in the central nervous system?". The search for scientific literature took place through the platform of the National Library of Medicine (NLM), which brings together records from the MEDLINE and PUBMED databases, by crossing the Health Sciences Descriptors (DeCS), together with the Boolean operators “AND” and “OR” in English in the years 2012 to 2022. This article considered complete publications, reviews, and experimental studies within the theme and with proposed descriptors. In total, 69 articles were selected, after applying the inclusion criteria, only 7 studies were included in the qualitative analysis of this work. The bibliographic survey showed that, in an animal model, the administration of alcohol, both acutely and chronically, can cause damage during adolescence to adulthood in the system. central nervous rhea. Despite the evidence presented, the scientific literature still needs more studies focusing on damage in females, mimicking the consumption behavior of women.